An optimization-driven design framework for inertance-integrated hydraulic shock absorbers: incorporating nonlinear and parasitic effects - He, Haonan; Wang, Zixiao; Li, Yiyuan; Song, Zhiguang (Springer, 2025)
Integrated spring-damper-inerter systems have been shown to outperform traditional damper-only absorbers in suppressing mechanical vibrations, driving interest in incorporating hydraulic stiffness, damping, and inertance components into automotive shock absorbers to enhance ride comfort. Extensive research has been conducted to identify the optimal absorber configuration from a vast design space. However, existing design approaches often neglect the nonlinear and parasitic effects (NPEs) inherent in hydraulic components and consider only limited topological layouts, thereby limiting the comprehensiveness and accuracy of the design space exploration. This oversight can result in discrepancies between simulated and real-world performance, potentially leading to suboptimal designs. To address this, a novel computer-aided engineering (CAE) framework is proposed for optimizing the configuration of inertance-integrated hydraulic shock absorbers. The framework follows a three-step process: (i) a graph-based method for enumerating all feasible hydraulic network layouts from a predefined catalog of components, (ii) an automated MATLAB subroutine for modeling these networks in Simscape, incorporating component models that explicitly account for NPEs, and (iii) a MATLAB-CarMaker co-simulation workflow for optimizing the hydraulic networks within a high-fidelity vehicle model. A case study involving a saloon car subjected to an ISO 8608 rough road input demonstrates the effectiveness of the framework. The optimized absorber design improves ride comfort by 17.6% when the NPE associated with hydraulic inertance realization is neglected and by 8.3% when it is considered, both while meeting dynamic tire load and suspension travel constraints. These results emphasize the importance of incorporating NPEs in the design process and validate the framework as an effective CAE tool for developing high-performance hydraulic absorbers for practical applications.
Keywords: 40 Engineering; 4010 Engineering Practice and Education; Design Practice & Management; 46 Information and computing sciences; Computer-Aided Engineering (CAD, CAE) and Design; Engineering Design; Engineering Fluid Dynamics; Mechanical Engineering; Vehicle engineering; Hydraulic Engineering